Legal Ideals Pancasila in the Development of a National Environmental Legal System - Rafiqi, Ilham Dwi (Audito Comparative Law Journal (ACLJ), 2023)
The discussion of legal ideals Pancasila in Indonesia has become a prolonged discourse and may not be final. This is motivated by the dynamics and problems of the nation and state in various sectors of life, one of which is the environmental sector. This paper aims to examine the potential for developing legal ideals in the national environmental law system. The research method used is normative legal research. The results of the study show that in its implementation the legal ideals of Pancasila are still not running as they should in the environmental sector in Indonesia. This is because there are deviations in values ​​in the preparation of legal policies and action agendas. In the development of a national environmental law system, legal ideals cannot be seen and read explicitly, but must continue to be explored and interpreted in every Pancasila value. The ideals of Pancasila law contain environmental values such as ecological, ecoreligious, ecosocial, and ecocracy values. The legal ideals of Pancasila are positioned and functioned as a way of life, guiding norms, and critical norms in the legal agenda in the environmental sector